"Time Enough at Last": On the Possibility of Universal Friendship in the Eschaton - Myrose, Jamie E. (Theological studies, 2026)
This article argues that friendship is not solely an analogy for eschatological life but can be an explicit object of eschatological hope. Responding to Gary Chartier's contention that universal eschatological friendship is impossible due to human finitude and the preferential nature of friendship, I engage John Thiel's account of time and forgiveness in the eschaton. I argue that our finite participation in the eternal life of God, as mediated by time, entails a transfiguration of our finitude that both respects and transcends our creaturely identities. This transfiguration makes universal eschatological friendship a reasonable hope and affirms earthly friendship as a site of eschatological anticipation.